CFP: Methods for Archival Silence in Early History, American Historical Review - Cheryl (Publishing in the Archives Profession, 2025)
The American Historical Review seeks proposals for a special issue illustrating a range of methodological approaches to archival silence developed by scholars of early history.
United States of America